Enhancement of Preventive Vaccination Approaches for Children with Health Problems: Prospective Cohort Study Results - Marina V. Fedoseenko; Leyla S. Namazova-Baranova; Elena A. Vishneva; Svetlana V. Tolstova; Arevaluis M. Selvyan; Tatiana A. Kaliuzhnaia; Firuza Ch. Shakhtakhtinskaya; Margarita A. Soloshenko; Tatiana E. Privalova; Maria V. Fominyh; Tatiana E. Zinovyeva (Union of pediatricians of Russia, 2021)
Background. Modern preventive vaccination is intended to protect and enhance the health of every person considering age and health issues. Vaccination of children with chronic diseases in our country remains extremely topical and arguable problem that associated with many pending issues for doctors of various specialties, including those working as primary care specialists.Objective. The aim of the study is to develop major approaches and to prove scientifically the efficacy and safety of preventive vaccination for children with various chronic diseases.Methods. We have conducted comprehensive study of 100 children aged from 1 month to 17 years 11 months. Children were divided into 4 groups according to the specific disease. Vaccinal and infectious history was analyzed. The post-vaccination period was estimated due to the results of the questionnaire completed by parents. Vaccination immunogenicity was estimated based on the results of the level of specific antibodies to various controlled infections (measles, rubella, parotitis, hepatitis B, pertussis, haemophilus influenza type b).Results. Protective titers of antibodies against haemophilus influenza type b were revealed in 96.2% of all examined patients, tetanus and hepatitis B - in 95.2%, against pertussis - in 92.5%, rubella - in 91%, measles - in 87.5%, parotitis - in 71.9%, chickenpox - in 69% children a month after the completed vaccination. The postvaccinal period was characterized as favorable in most patients. Major changes in overall health status occurred after vaccination in 42% of children was the following: subfebrile fever, capriciousness, or fatigue. Local reactions have developed only in 15% of cases.Conclusion. The results of this study have demonstrated the preventive vaccination efficacy and safety in children with various chronic diseases